Hubungan Penggunaan Obat Tradisional Dengan Kualitas Hidup Pada Anak Muda Penderita Hipertensi di Kota Jambi - Qonita Salsabila; Yuni Andriani; Amraini Amelia (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension “is one of the non-communicable diseases that is currently increasingly found, not only in the elderly but also in young people. In addition to undergoing therapy using antihypertensive drugs, some hypertension sufferers use traditional medicine as a complementary therapy to help control blood pressure. This study aims to analyze the relationship between the use of traditional medicine and the quality of life in young people with hypertension in Jambi City. This study uses a quantitative method with an analytical observational design through a cross-sectional comparative approach. The number of samples in this study was 50 respondents selected using the WHOQOL-BREF questionnaire, then analyzed using the SPSS program through the Independent Sample T-Test and multiple linear regression. The results of the study showed a difference in the quality of life between respondents who used traditional medicine and respondents who did not use traditional medicine with a significance value of 0.018 (p <0.05). However, the results of multiple linear regression analysis show that the variables of traditional medicine use, age, gender, duration of hypertension, and blood pressure simultaneously do not have a significant relationship with the respondents' quality of life, with a significance value of 0.054 (p>0.05).